2013
DOI: 10.1111/iji.12052
|View full text |Cite
|
Sign up to set email alerts
|

High susceptibility to pemphigus vulgaris due to HLA‐DRB1*14:54 in the Slovak population

Abstract: The current work describes an association between pemphigus vulgaris (PV) and class II HLA alleles in the Slovak population, the first such study in Slovakia on the 'high-resolution level'. This work takes into account the new HLA allele nomenclature, officially adopted in 2010. In particular, we have focused on the associations between PV and DRB1*14:54 and DRB1*14:01. This case-control study was performed in a cohort of 43 PV Caucasian patients and 113 Caucasian control subjects from Slovakia. HLA typing was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 20 publications
5
27
0
3
Order By: Relevance
“…No association of DRB1*14:01 with PV was found. Similar findings (association of PV with DRB1*14:04 and not *14:01 ) are recorded in Slovakian, Pakistani, Indians, white European and Indo Asian patients in Great Britain .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…No association of DRB1*14:01 with PV was found. Similar findings (association of PV with DRB1*14:04 and not *14:01 ) are recorded in Slovakian, Pakistani, Indians, white European and Indo Asian patients in Great Britain .…”
Section: Discussionsupporting
confidence: 82%
“…However, inheritance of certain human leukocyte antigen (HLA) alleles is believed to be the most probable predisposing factor . Most literature on the genetic susceptibility to PV is focused on the investigation of major HLA genes . Due to the linkage disequilibrium (LD) – the non‐random association of alleles at different loci, the occurrence of disease‐associated alleles in haplotypes in various autoimmune diseases including PV, is obvious .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies, often utilizing serum, have addressed the HLA haplotype distribution utilizing ABD cases and controls [5,6,[12][13][14][15]. These studies concluded that some HLA alleles strongly predispose toward and/or protect against ABDs.…”
Section: Discussionmentioning
confidence: 99%
“…The meta‐analysis of Yan et al does not mention HLA‐DRB1*14:54 , but describes a strong association to HLA‐DRB1*14:01 , whereas Saha et al reported that HLA‐DRB1*14:54 , but not HLA‐DRB1*14:01:01 , is associated with PV in a British cohort . Similarly Parnicka et al reported an association to HLA‐DRB1*14:54 and PV in Slovakians .…”
Section: Low Resolution Genotyping Of Hla‐drb1 In German Pemphigus Vumentioning
confidence: 99%